2001
DOI: 10.1080/02671520110058688
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in school: nature, effects and remedies

Abstract: This review synthesizes recent research on bullying in school, a widespread social problem among school-age children in many countries. It begins with a theoretical examination of the de® nition of bullying, showing the multifaceted coercive behaviours of bullying. The review proceeds to demonstrate the short-and long-term consequences of bullying for both victims and bullies. The authors outline individual characteristics of victims, bullies and bystanders as well as school characteristics of bullying. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
10
0
4
Order By: Relevance
“…School level predictors are often divided into two different categories: school context and school climate (Ma, Stewin, & Mah, 2001;Payne & Gottfredson, 2004). School context refers to structural characteristics such as school size and the neighborhood's socioeconomic status (SES).…”
mentioning
confidence: 99%
“…School level predictors are often divided into two different categories: school context and school climate (Ma, Stewin, & Mah, 2001;Payne & Gottfredson, 2004). School context refers to structural characteristics such as school size and the neighborhood's socioeconomic status (SES).…”
mentioning
confidence: 99%
“…Οι θύτες είναι συνήθως παιδιά με χαμηλό αυτοσυναίσθημα (Griffin, & Gross, 2004), θύματα ενδοοικογενειακής βίας και μαθητές μέτριων ή χαμηλών σχολικών επιδόσεων (Ma, Stewin, & Mah, 2001). Τα αγόρια-θύτες χρησιμοποιούν κυρίως το σωματικό και τον ηλεκτρονικό εκφοβισμό, ενώ τα κορίτσια-θύτες εκφοβίζουν έμμεσα, συνήθως, κορίτσια ίδιας ηλικίας.…”
Section: το φαινόμενο «σχολικός εκφοβισμός»unclassified
“…Τα θύματα είτε είναι παθητικά ή πειθήνια θύματα, δηλαδή παιδιά αγχώδη, ευαίσθητα, υποχωρητικά και σωματικά περισσότερο αδύναμα, είτε προκλητικά θύματα, δηλαδή παιδιά επιθετικά, που προκαλούν ένταση στο περιβάλλον τους και συγκρούονται διαρκώς με αυτό. Έχουν βιώσει απόρριψη από τους γονείς τους, έχουν χαμηλή αυτοεκτίμηση και χαμηλές σχολικές επιδόσεις (Ma, Stewin, & Mah, 2001). Στους παρατηρητές, κορίτσια ή αγόρια, έχουν αποδοθεί περαιτέρω χαρακτηρισμοί όπως «μάρτυρες», «συμμετέχοντες» ή «περαστικοί» (Stassen-Berger, 2007).…”
Section: το φαινόμενο «σχολικός εκφοβισμός»unclassified
“…The report further revealed that bullies exhibit behaviors deigned to undermine their victim's professional standing, authority and competence or impede access to key resources for their work. A school with high bullying syndrome scares new students (Ma Xin Len Stewin & Deveda, 2001;Aluede and Fajoju, 2011;Al Fassi, 2004). Thus bullying can frustrate the victim in many ways, making him/her not to be able to attain his/her goals.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…He continued by saying that bullying has to occur repeatedly and regularly and over a period of time. Bullying is characterized by acts of intentional harm, repeated over time, in a relationship where an imbalance of power exists (Pepler and Craig, 2007;Ma Stewin and Mah, 2001). Bullying is not just a child's play but a terrifying experience faced by many school children every day (Craig, 1998;Beran, 2005;and Thornbery 2010).…”
Section: Introductionmentioning
confidence: 99%